Tamblang Waluh: Transformasi Ajaran Karma Marga Yoga dalam Tradisi Lokal Bali Timur - Sugata, I Made (Institut Hindu Dharma Negeri Denpasar, 2018)
The Vedic concepts gave birth to Balinese noble culture that is implemented through the teachings of karma mÄrga. The effort to preserve the culture cannot be separated from the teachings of Hinduism which originates to the teachings of karma mÄrga yoga. In Bungaya Village, Bebandem District, Karangasem Regency there is a unique culture and full of creativity from young people. The culture is Tamlang Waluh tradition implemented by Teruna Desa. This tradition is unique because at the time of its execution, participants who follow the tradition pronounce words bojrag (porn) but has a deep meaning. The spoken word like â€œceli katukâ€, based on the ethical view is inappropriate but based on the philosophical view that contains the meaning of the process of creation. The transformation of the teachings of karma mÄrga yoga in Tamlang Waluh tradition is the transformation of theology as the philosophical foundation of sujud bhakti before Ida Sang Hyang Widhi Wasa trhough His manifestation as Purusa Pradana. Besides, improving the teachings of Susila (Ethics) is seen in the process of metinjakan that the younger generation is educated to always uphold the teachings of Tri Kaya Parisudha ie do not harm the opponent, do not speak harsh words, and do not hold a sense of resentment.